Misoprostol - A Wonder Drug (Bangladesh Journal of Medical Science, 2012)
Misoprostol is a synthetic analogue of natural prostaglandin E1. It has a very convenient and flexible drug dosing, can be administered orally, sublingually, buccally, rectally and by vaginal route. Misoprostol is useful for elective early medical abortion, cervical ripening in surgical abortion as well as in gynecological D & C, mid trimester abortion, cervical ripening and induction of labour in live or dead fetus as well as in prevention and treatment of PPH. Key words: Misoprostol; medical abortion; induction of labour; postpartum hemorrhage.DOI: http://dx.doi.org/10.3329/bjms.v10i4.9490BJMS 2011; 10 (4): 221-225